Clinical profile and outcome of antineutrophil cytoplasmic antibody-associated vasculitis: A retrospective observational study from South India - Sham Santhanam; Hema Murugesan; Kavitha Mohanasundaram (Indian Journal of Rheumatology)
Aim: The aim was to study the clinical profile and outcome of patients with antineutrophil cytoplasmic antibody-associated vasculitis (AAV). Methods: This was a retrospective observational study of patients with a diagnosis of AAV (granulomatosis with polyangiitis [GPA], microscopic polyangiitis [MPA], and eosinophilic granulomatosis with polyangiitis [EGPA]). Patient records from January 2015 to December 2020 were retrieved and included in the analysis. We used the European Medicines Agency (EMA) algorithm for classification of patients. Results: Forty (14 males and 26 females) patients were included (34 – GPA, 4 – MPA, and 2 – EGPA). The median age was 48 years (54.5 – males and 46 – females). The median disease duration was 6 months, and the median follow-up duration was 18.5 months. As per European Vasculitis Society disease categorization, 25 had organ/life-threatening type, 10 had rapidly progressive renal failure/pulmonary hemorrhage, 4 nonorgan threatening, and 1 refractory disease. The median erythrocyte sedimentation rate (mm/h) and C-reactive protein (mg/L) were 64 and 52.49, respectively. The median Birmingham Vasculitis Activity Score was 15.5. Twenty-six had constitutional features, 22 musculoskeletal, 24 pulmonary, 19 renal, 13 ocular, 13 ENT involvement, 10 mucocutaneous, 11 peripheral nervous system, 1 central nervous system, and 3 had cardiovascular involvement. As induction therapy, cyclophosphamide was used in 15 and rituximab in 20 patients. Conclusion: The age of onset of AAV was relatively delayed in comparison to other Indian studies. We had female predominance similar to other Indian studies but in contrast to European and US cohorts. In comparison to other Indian studies, prevalence of ENT and ocular manifestations were less and none of the subjects had gastrointestinal involvement.